Syntheses, structures, and magnetic properties of acetate-bridged lanthanide complexes based on a tripodal oxygen ligand - Sheng, Yu; Jiang, Yu-Jing; Cheng, Zi-Hang; Liu, Ru-Chan; Ge, Jing-Yuan; Gao, Feng (Frontiers in Chemistry, 2022)
Four homodinuclear lanthanide complexes, Dy2 (LOEt)2(OAc)4 (1), Tb2 (LOEt)2(OAc)4 (2), Ho2(LOEt)2(OAc)4 (3), and Gd2 (LOEt)2(OAc)4 (4), have been synthesized and characterized based on a tripodal oxygen ligand Na [(η5-C5H5)Co(P(O)(OC2H5)2)3] (NaLOEt). Structural analyses show that the acetate anions bridge two symmetry-related Ln3+ ions in the μ2:η1:η1 and μ2:η1:η2 coordination patterns, and each lanthanide (III) ion owns a twisted square antiprism (SAPR) conformation. Static magnetic measurements reveal the weak intramolecular ferromagnetic interaction between dysprosium (III) ions in 1 and antiferromagnetic Ln3+···Ln3+ couplings in the other three complexes. Through the analysis of the ligand-field effect and magnetic anisotropy axis orientation, the reasons for the lack of dynamic magnetic behavior in 1 were identified.